PENGARUH HARGA, KUALITAS PRODUK DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN MINUMAN XING FU TANG (STUDI PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH YOGYAKARTA) - Hariyanto, Muhsin; Alviansyah, Izzudin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to partially and simultaneously test the influence of price, product quality and halal label on the purchasing decision of Xing Fu Tang beverage. This research is a descriptive quantitative study. The population in this study was students of Universitas Muhammadiyah Yogyakarta who bought Xing Fu Tang beverage, while the sample collected in this study was as many as 42 respondents. The sampling technique used accidental sampling techniques. The data obtained was then analyzed using Structural Equation Modeling (SEM) with the help of the SmartPLS 3.0 application. The results of this study showed that the variables of price and product quality had a positive and significant effect on the purchasing decision of Xing Fu Tang beverage, while the variable of halal label had no significant effect on the purchasing decision of Xing Fu Tang beverage.